2007
DOI: 10.1002/er.1320
|View full text |Cite
|
Sign up to set email alerts
|

Experiment and simulation investigations for effects of flow channel patterns on the PEMFC performance

Abstract: SUMMARYExperiments and simulations are presented in this paper to investigate the effects of flow channel patterns on the performance of proton exchange membrane fuel cell (PEMFC). The experiments are conducted in the Fuel Cell Center of Yuan Ze University and the simulations are performed by way of a three-dimensional full-cell computational fluid dynamics model. The flow channel patterns adopted in this study include the parallel and serpentine flow channels with the single path of uniform depth and four pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 34 publications
0
21
0
1
Order By: Relevance
“…Studies concerning to thermal-hydraulic characteristics and effects over the behavior in PEMFCs have been carried out [4,5]. Additionally, some experimental measurements and analytical studies related to the GDL structures and performance have been realized [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies concerning to thermal-hydraulic characteristics and effects over the behavior in PEMFCs have been carried out [4,5]. Additionally, some experimental measurements and analytical studies related to the GDL structures and performance have been realized [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Changing the pattern of the flow channels of a PEM fuel cell was studied by Ferng et al . . They conducted experimental investigation as well as a computational fluid dynamic simulation of a three‐dimensional model.…”
Section: Introductionmentioning
confidence: 99%
“…Boddu et al developed various modified flow channel configurations and found that serpentine square bends showed higher pressure drops compared with curvilinear bends. Ferng et al studied the influence of different channel patterns on the fuel cell performance and found that different depth patterns played an important role in the fuel cell performance with parallel channels. Imbrioscia et al studied the gas flow behaviors considering the width, depth, and shape of the flow channel based on a 3D fuel cell model and revealed that a suitable position of obstruction nearby the gas inlet would improve the flow management.…”
Section: Introductionmentioning
confidence: 99%